Optimization and characterization of lipase-catalyzed synthesis of palm amino acid surfactant - Bidin, Hasmah (2009)
Optimization and characterization of lipase-catalyzed synthesis of palm amino acid surfactant was studied in 500 mL stirred tank reactor (STR). The reaction of palm kernel olein (PKO) and L(+)-lysine with Lipozyme RM IM as biocatalyst was optimized by response surface methodology (RSM). The study was divided into five parts which are; the optimization of reaction synthesis, the reactor study in term of mixing efficiency, the stability of immobilized enzyme, the purification process and the analysis and characterization of palm amino acid surfactant. A two level (24) full factorial central composite rotatable design (CCRD) was successfully employed for the experimental design and analysis of the results. The combined effect of temperature (XI); (40.0- 70.0°C), impeller speed (X2); (100.0-400.0 rpm), substrate molar ratio (X3); (1.0-4.0 mmol) and amount of enzyme (X4); (5.0-8.0 g) was investigated. The optimum condition derived via RSM at fixed reaction time of 24 h was successfully optimized at temperature; 47.50°C, impeller speed; 324.00 rpm, substrate ratio; 3.25 mmol and amount of enzyme; 7.25 g. The actual experimental yield was 89.03% under the optimum condition, which compared well with the maximum predicted value of 93.77%. Reactor study on the performance of 2 L STR as a mixing device was evaluated to improve the mixing efficiency. The reaction was scaled-up to 360X with a total volume of 1.125 L. The rheological property of the reaction mixture exhibited Newtonian behaviour. Rushton turbine impeller showed better performance in degree of mixing, whereby a high Reynold number for a range between 102 and 104 was achieved from 100-400 rpm, which exhibited a transitional flow pattern as compared to AL hydrofoil impeller. The Lipozyme RM IM was shown to be quite stable based on its synthetic activity where the percentage yield of palm amino acid surfactant was decreased only after 4 recycles in STR. The effect of shear forces due to the mechanical impeller speed on the enzyme morphology was determined by scanning electron microscope (SEM). The percentage yield of palm amino acid surfactant was found to be low for Rushton turbine impeller and AL hydrofoil impeller with speed of 400 rpm and 200-400 rpm, respectively.Purification process was successfully studied using liquid-liquid extraction technique, whereby high purity, 96.97% of palm amino acid surfactant was obtained. Analysis of the surfactant was determined by Fourier transform-infrared spectroscopy (FT-IR) and gas chromatography-flame ionization detector (GC-FID) to verify the identity and purity of the product isolated. Characteristics of palm amino acid surfactant were also examined, which include saponification value, acid value, iodine value and ester value Compatibility of the surfactant in most oils and its stability even after heating up to 90°C and overnight storage at room temperature showed that the surfactant has good potential to be used for further applications.